Ethanol-Induced Hepatic Insulin Resistance is Ameliorated by Methyl Ferulic Acid Through the PI3K/AKT Signaling Pathway - Cheng, Qi; Li, Yong Wen; Yang, Cheng Fang; Zhong, Yu Juan; Li, Li (Frontiers in Pharmacology, 2019)
One of the key event during the development of alcoholic liver disease (ALD) is that alcohol inhibits the insulin signaling pathway in liver and leads to disorders of glucose and lipid metabolism. Methyl ferulic acid (MFA) is a biologically active monomer isolated from the root of Securidaca inappendiculata hasskarl. It has been reported that MFA has a hepatoprotective effect against alcohol-induced liver injury in vivo and in vitro. However, the effect of MFA on ethanol-induced insulin resistance in alcoholic liver disease (ALD) remains unclear. In this study, we investigated whether MFA could exert protective effects against hepatic insulin resistance in ethanol-induced L-02 cells and ALD rats. ALD was induced in vivo by feeding a Lieber-DeCarli diet containing 5% (w/v) alcohol for 16 weeks in Sprague-Dawley rats. Insulin resistance was induced in vitro in human hepatocyte L-02 cells with 200 mM ethanol for 24 h followed by 10-7 nM insulin for 30 min. MFA exhibited the effects of inhibited insulin resistance, reduced the enzymatic capacity for hepatic gluconeogenesis and increased hepatic glycogen synthesis both in vivo and in vitro. In addition, the results of transcriptome sequencing of liver tissues in the ethanol group and MFA-treated group indicated that "pyruvate metabolism", "glycolysis/gluconeogenesis" and "fatty acid metabolism" were significantly different in the ethanol group and MFA-treated group. Further studies suggested that MFA activated the hepatic phosphatidylinositol 3-kinase (PI3K)/AKT pathway in vivo and in vitro. Taken together, these findings suggested that MFA effectively ameliorated hepatic insulin resistance in alcoholic liver disease at least partially through acting on the PI3K/AKT pathway.